The impact of visual and tactile intervention in a learning environment essential for children with down syndrome - Espesor, Noelle Justine B.
Children?s development is affected by the physical environment that they are exposed to. In a learning place, it influences the children?s learning and concentration capability. Children with Down syndrome are suffering developmental delay which means having learning and concentration difficulties. They are prone to sensory sensitivities or they have sensory impairments. Moreover, children with Down syndrome are visual learners and they can also benefit from experiencing tactile opportunities. Thus, by developing visual and tactile interventions, the strengths and opportunities for children with DS will be utilized enhancing their disposition and wellbeing. A learning place planned and organized well is essential in dealing with the sensory sensitivities of the children. To determine the visual and tactile sensitivities and preferences of children with Down syndrome, utilizing study analysis on various materials which will stimulate the visual and tactile senses of children with DS was done. Direct observation in the schools was conducted in order to know the visual and tactile conditions of each school; survey questionnaire using the Wong Baker FACES Rating Scale was answered by 26 students with Down syndrome to determine the visual impact of colors, light, and patterns for them; the Maze Activity tool was participated by the same number of respondents to know which soft and hard material and its texture they preferred and give positive response to; then the analysis observation based on FLACC behavioral sensitivity scale was done to know the response of each student to each architectural material included in the maze activity tool. As a tool of analysis on the aforementioned research tools, statistical analysis frequency was used to know the common visual and tactile conditions of the schools where the study was conducted. The research showed that both schools have plain walls painted white and are using fluorescent light. Through weighted mean, the effect of different visual sensory stimuli to children with DS was analyzed. The research found that bright colors, natural white light, and plain materials are best for children with DS. And through statistical analysis frequency, the effect of different tactile sensory stimuli to children with Ds was analyzed. The research found that shag carpet for soft materials, and vinyl tile for hard materials were preferred, and given positive response to by the children with DS. The results became the cornerstone on creating a design guideline of a physical learning environment effective to develop an improved disposition for children with Down syndrome by focusing on visual and tactile interventions in their environment.